1977
DOI: 10.1038/bjc.1977.250
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Metabolic Determinants of Resistance to Azo-dye and Susceptibility to Nitrosamine Carcinogenesis of the Guinea-pig

Abstract: Summary.-During diethylnitrosamine (DEN) administration, a distinctive difference was observed between rats and guinea-pigs in the sequence of ultrastructural changes in the hepatic endoplasmic reticulum (ER). In DEN-induced hepatic tumour cells in the guinea-pig there was extensive proliferation of the rough ER, while the smooth ER was quite sparse; in the premalignant liver the opposite was noted. This is in contrast to the rat, in which administration of either DEN or 3'-methyl-4-dimethylaminoazobenzene (3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…3'Me-DAB forms t-RNA- azo dye complex in liver of rats, which is considered as the major target for this azo carcinogen[ 9 ]. Nonetheless, literature has indicated that the carcinogenicity of azo dyes varies with the species tested [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…3'Me-DAB forms t-RNA- azo dye complex in liver of rats, which is considered as the major target for this azo carcinogen[ 9 ]. Nonetheless, literature has indicated that the carcinogenicity of azo dyes varies with the species tested [ 10 ].…”
Section: Introductionmentioning
confidence: 99%